Sarcomatoid Carcinoma of the Oral Cavity: A Diagnostic Dilemma - Anshul Mahajan; Sujata Mohanty; Sujoy Ghosh; Aadithya B. Urs; Nita Khurana; Sunita Gupta (Case Reports in Dentistry)
Sarcomatoid carcinoma (SC) is a rare variant of squamous cell carcinoma which is characterized by a dysplastic epithelial component and a stromal element with invasive fusiform or spindle-shaped cells. The clinical and histopathologic characteristics make it very difficult to distinguish SC from epithelioid sarcoma (ES). We present a case of a 51-year-old man with a soft tissue mass in the oral cavity diagnosed as proximal variant of epithelioid sarcoma on incisional biopsy. A thorough radiologic examination was conducted to rule out the possibility of a primary elsewhere in the body. Supraomohyoid neck dissection, mandibular resection, and reconstruction with recon plates were carried out. Histopathologic examination was suggestive of epithelioid variant of SC which was contrary to the incisional biopsy report. The dilemma in diagnosis was resolved by observing the presence of invading atypical epithelial cells into the stroma confirming the epithelial origin of the tumor.